OPTIMIZING BRIQUETTE CHARACTERISTICS BASED ON THE RATIO OF BAMBOO AND COCONUT FIBER UNDER CONVENTIONAL METHOD - Anggorowati, Dwi Anna; A.S., Mardhiyah; N., Rizky; K., Ido; Adam Yonanda; Jamilulchal , M (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2024)
This study aims to optimize the potential of biobriquettes produced from a mixture of bamboo and coconut fiber using starch adhesive. The focus of the research includes determining the composition ratio of bamboo and coconut fiber that gives the best results, as well as the physicochemical characteristics of the briquettes, including moisture content, volatile matter, ash content, and calorific value. In the carbonization process, bamboo is processed for 5 hours, while coconut fiber is processed for 2 hours, with an operating temperature of 140°C. This study considered variations in the ratio of bamboo and coconut fiber mixture, such as 1:1, 5:1, and 9:1. Starch adhesive was used in a concentration of 25% of the total mixture as a determining factor in the formation of biobriquettes. The results showed that the bamboo:coconut fiber mixture ratio of 5:1 gave the best biobriquette characteristics. These briquettes have low moisture content, optimal volatile matter, standard ash content, and high calorific value of 5679.15 cal/gram. Carbonization at 140°C positively influenced the physicochemical properties of the biobriquettes.